2015
DOI: 10.1080/02640414.2015.1024712
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age on haematological markers pre- and post-marathon running

Abstract: This study investigated whether haematological markers differ between young and masters marathon participants, running at similar performance levels. Nine young (31.89 ± 4.96 years) and eight masters (63.13 ± 4.61 years) runners participated. At five time points (pre-race through 54 h post-race), a complete blood cell count, basic metabolic panel and creatine kinase (CK) isoenzyme panel were assessed. Race performance was standardised using the World Masters Association Age Grading Performance Tables. Total CK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
8
0
2
Order By: Relevance
“…Although, CK values were higher for the young cyclists it was deemed to be not practically significant with normal reference values for CK in athletes suggested to be 82 -1083 U•L -1 (Mougios, 2007). Furthermore, previous studies reporting muscle damage in masters athletes have reported increases of 542% and 1050% of baseline CK values following marathon (Martin et al, 2015) and trail running (Easthope et al, 2010), which again, when compared to the 10% increase seen in the present study suggests that the CK values in the present study were not representative of exercise induced muscle damage. Finally, the current study supports previous research that showed similar CK concentrations (100 -200 U•L -1 ) over three days of consecutive endurance cycling with no significant difference in the CK response of masters athletes and young cyclists (Fell et al, 2006).…”
Section: Discussionmentioning
confidence: 72%
“…Although, CK values were higher for the young cyclists it was deemed to be not practically significant with normal reference values for CK in athletes suggested to be 82 -1083 U•L -1 (Mougios, 2007). Furthermore, previous studies reporting muscle damage in masters athletes have reported increases of 542% and 1050% of baseline CK values following marathon (Martin et al, 2015) and trail running (Easthope et al, 2010), which again, when compared to the 10% increase seen in the present study suggests that the CK values in the present study were not representative of exercise induced muscle damage. Finally, the current study supports previous research that showed similar CK concentrations (100 -200 U•L -1 ) over three days of consecutive endurance cycling with no significant difference in the CK response of masters athletes and young cyclists (Fell et al, 2006).…”
Section: Discussionmentioning
confidence: 72%
“…Em uma pesquisa, realizada nos Estados Unidos com participantes jovens de uma maratona, foram encontrados níveis plasmáticos aumentados e sustentados da CK-MB em até 54 horas pós exposição ao exercício. 20,21 Indivíduos treinados, que realizam exercício de alta intensidade em práticas esportivas, tendem durante o teste de esforço máximo apresentar de forma aguda maiores elevações séricas da CK-MB do que indivíduos não treinados, sugerindo assim um envolvimento cardíaco e principalmente benigno na natureza desses níveis séricos. 22 Cientistas também verificaram o efeito do exercício prolongado e das variações de temperatura ambiental no comportamento das creatina quinases e identificaram que quanto mais prolongado o exercício e maior a temperatura ambiental, maiores são as liberações plasmáticas desses biomarcadores.…”
Section: Discussionunclassified
“…10 (4 F and 6 M) recreational runners *6 Kobayashi et al 12) 15 M recreational runners NS Kyröläinen et al 13) 7 (1 F and 6 M) trained triathletes NS Liang et al 46) 15 recreational runners NS Martin et al 47) 17 M recreational runners Soeder et al 48) 11 M runners Takayama et al 17) 7 (2 F and 5 M) recreational runners NS Takayama et al 18) 7 M recreational runners NS Tojima et al 49) 11 M recreational runners NS Blanks indicate no data reported.…”
mentioning
confidence: 99%